2000
DOI: 10.1103/physrevd.62.024005
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal nature of incipient extremal black holes

Abstract: We examine particle production from spherical bodies collapsing into extremal Reissner-Nordström black holes. Kruskal coordinates become ill-defined in the extremal case, but we are able to find a simple generalization of them that is good in this limit. The extension allows us to calculate the late-time worldline of the center of the collapsing star, thus establishing a correspondence with a uniformly accelerated mirror in Minkowski spacetime. The spectrum of created particles associated with such uniform acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(138 citation statements)
references
References 32 publications
(59 reference statements)
4
134
0
Order By: Relevance
“…The Euclidean topology of an extremal black hole is relatively trivial, and this effectively eliminates the usual horizon contribution (which accounts for the non-extremal entropy [9]) to the Euclidean action. Note that the findings of various other works have since supported the Hawking conjecture [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The Euclidean topology of an extremal black hole is relatively trivial, and this effectively eliminates the usual horizon contribution (which accounts for the non-extremal entropy [9]) to the Euclidean action. Note that the findings of various other works have since supported the Hawking conjecture [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 65%
“…To help clarify this apparent conflict, we take note of recent findings by Liberati et al [14]. They have considered an extremal Reissner-Nordstrom black hole undergoing collapse and demonstrated that (in spite of asymptotic particle production) the temperature remains undefinable on account of a non-Planckian distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Liberati, et al [4] pointed out that the generalization to extremal black holes from nonextremal black holes is not trivial. One important difference is that the Kruskal transformation for non-extremal black holes, which plays a crucial role in computing the particle creation, breaks down for extremal black holes.…”
Section: Introductionmentioning
confidence: 99%
“…The arguments in [4] are reviewed briefly here as follows. Start with the usual form of the Reissner-Nordström (RN) geometry with parameters Q and M…”
Section: Introductionmentioning
confidence: 99%